Economics analysis of rice - fish sequential farming system In the low lying paddy fields of Kuttanad, Kerala - Shanat K Mathew (Department of Agricultural Economics, College of Horticulture, 2001)
The present study on "Economic analysis of rice-fish sequential farming system in the low lying paddy fields of Kuttanad, Kerala" was aimed to analyse comparative economics of rice monocropping and rice-fish sequential farming systems, to quantity the employment generation capacity of the integrated system and to identify the constraints in the wide spread adoption of rice-fish sequential farming system. The study was undertaken during May - July 2000 and the data pertains to the year 1999. Data for the study was generated through sample survey of farmers by personal interview method using a pretested structured interview schedule. The study was conducted with a sample of 100 farmers for each system of cultivation. Two stage random sampling was adopted for the study. Tabular analysis was used to analyse the data. The cost of cultivation (cost C3) of rice under monocropping (Rs.23419.47 per hectare) and of rice under sequential farming system (Rs.1972S.31 per hectare) Was estimated. For fish, the cost of cultivation per hectare was Rs.6768.39. The major expenditure on input for rice cultivation under both systems and for fish was human labour. In rice monocropping, land preparation was observed to be the most expensive operation, whereas, in sequential farming weeding was the most expensive operation. In the case of fish cultivation, harvesting of fish turned out to be the most cost consuming operation. Gross income per hectare realized from the main as well as by product at the aggregate level was Rs.2S252.50, Rs.28371.00, and Rs.8782.95 for rice (monocropping), rice (sequential farming) and fish respectively. Cost of production per quintal of rice (monocropping) was Rs.64S.16 and for rice (sequential farming) was Rs.482.0S. For fish, cost of production per quintal of fish estimated to be Rs.1538.62.